PARADIGMATIC AGE SHIFT OF HYPERTENSION DISEASE: A STUDY AMONG YOUNG ADULTS - Pandey, Dhurvendra; Guleri, Sunil kant; Sinha, Umesh; Pandey, Smriti; Tiwari, Shivam (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives of study are to assess the magnitude of hypertension and identify various factors associated with hypertension among participants. Methods: A cross-sectional study done on attendees and patients coming to medicine OPD in a tertiary care hospital in Madhya Pradesh. The earlier diagnosed hypertensive cases were excluded from the study and 500 participants were studied. Clinical measurements and predesigned semi-structured questionnaire were used for data collection. Chi-square test was applied to find association of risk factors with hypertension. Results: About 21.6% of the participants were diagnosed for hypertension. The increasing age, obesity, smoking, alcoholism, and daily salt intake above two teaspoonfuls had significant association with occurrence of hypertension (p≤0.05). Conclusion: The magnitude of hypertension is increasing among adult population and has strong association with increasing age and other risk factors. Hence, the early diagnosis with the help of screening tools is needed. Opportunistic screening of all adults coming in contact of health system will help the pool of diagnosed cases of hypertension and help to reduce burden of complications caused by hypertension.